Production of blue-colored polyhydroxybutyrate (PHB) by one-pot production and coextraction of indigo and PHB from recombinant Escherichia coli - Jung, Hye Rim; Choi, Tae Rim; Han, Yeong Hoon; Park, Ye Lim; Park, Jun Young; Song, Hun Suk; Yang, Soo Yeon; Bhatia, Shashi Kant; Gurav, Ranjit; Park, Hyun A.; Namgung, Seyun; Choi, Kwon Young; et al. (Dyes and Pigments, 2020)
Polyhydroxyalkanoate (PHA) is a promising substitute for petroleum-based plastics. For economically feasible and sustainable production of PHA, various strains and feedstocks have been reported till date, using which, polyhydroxybutyrate (PHB) could be produced on a large scale. However, the sensory characteristics of PHA, such as color, limit its further application in industries related to packaging, textiles, and medical materials. In this study, we investigated the feasibility of simultaneous production of indigo and PHB in recombinant Escherichia coli to generate colored bioplastics. With that objective, one-pot production and extraction of both indigo and PHB were successfully performed, and biotransformation of indole to indigo was reinforced by the introduction of PHA synthetic genes. Upon further investigation of the factors responsible for the increased indigo production, groEL and grpE, related to heat-shock proteins, and CYP102G4, were found to be up-regulated when analyzed by semi-quantitative reverse transcription-PCR. In the thermograms analyzed by thermal gravimetric analysis and differential scanning calorimetry, there was no notable difference between PHB and PHB-indigo film, implying that indigo did not affect the thermal properties of PHB itself. Overall, this study demonstrates the production of blue-colored PHB and enhanced production of indigo by the introduction of PHA synthetic genes.
Keywords: Indigo; One pot process; Poly-hydroxyalkanoate; Polyhydroxybutyrate; Recombinant Escherichia coli; Reverse transcription PCR; Sensory characteristics; Thermal gravimetric analysis; Colored polyhydroxyalkanoate; Escherichia coli; Indigo; One-pot process; Polyhydroxybutyrate